Protective Effect of Hydroxytyrosol on LPS-Induced Inflammation and Oxidative Stress in Bovine Endometrial Epithelial Cell Line - Enrico Gugliandolo; Roberta Fusco; Patrizia Licata; Alessio Filippo Peritore; Ramona D’amico; Marika Cordaro; Rosalba Siracusa; Salvatore Cuzzocrea; Rosalia Crupi (Veterinary Sciences, 2020)
Bovine endometritis is a serious pathogen-induced infectious disease that affects the physiological processes of estrus, pregnancy and the postpartum condition. The inflamed endometrium responds by activating an inflammatory intracellular signaling cascade that leads to increased expression of proinflammatory cytokines and reactive oxygen species (ROS). Oxidative stress is closely related to several pathological conditions in perinatal dairy cows and play a key role in tissue damage. Hydroxytyrosol (HT), a natural phenolic alcohol with a strong antioxidant activity, displayed a wide range of biological effect. The aim of this study was to evaluate the protective effects of HT in an in vitro model of lipopolysaccharide (LPS)-induced inflammation in bovine uterine endometrial cells. Our results showed that HT had a significant protective effect in LPS-induced inflammation and oxidative stress. HT was also able to increase the capacity of endogenous antioxidant systems through the up-regulation of the NRF2 pathway. Furthermore, HT restored the tight junction protein expressions. In conclusion, our results showed the protective effects of HT in LPS-stimulated BEND cells. Therefore, the results of this study suggest an important protective role of HT in the treatment and prevention of uterine pathologies in dairy cows.